Beyond the myths and magic of mentoring : how to facilitate an effective mentoring program - MURRAY, MARGO (Jossey-Bass Pub. San FranciscoUS, 1991)
Distinguishes between role model, sponsor and mentor. Identifies the components of a typical mentoring programme, but discusses 7 variations to show how the programme can be adapted to serve a variety of needs. Details how to select competent mentors and suggests strategies for matching proteges with compatible mentors. Emphasises the need for diagnostic, formative and summative evaluation.